Pengaruh Content Marketing, Influencer Marketing Dan Viral Marketing Terhadap Keputusan Pembelian Food And Beverage Kedai Kopi Jasa Ayah (Studi Kasus Pada Konsumen Kedai Kopi Jasa Ayah Di Kota Malang) - Syamsuddin, Muhammad Da’i; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The objective of this research is to evaluate the influence of content marketing, influencer marketing, and viral marketing on purchasing decisions for food and beverages at Kedai Kopi Jasa Ayah. By conducting this study, it is expected to provide a significant influence on purchasing decisions and to find out how content marketing, influencers, and viral marketing influence consumer purchasing, and to find out how content marketing, influencers, and viral marketing influence consumer purchasing decisions. This study uses the explanatory research method through a quantitative approach, sampling through non-probability with a purposive sampling method with a total of 99 respondents who are consumers who have made purchases at Kedai Kopi Jasa Ayah. Data collection was carried out by conducting questionnaires and analysis using SPSS statistical software.The results of this study indicate that content marketing, influencer marketing, and vial marketing have a simultaneous influence on purchasing decisions and each independent variable of content marketing, influencer marketing, and viral marketing has a partial influence on purchasing decisions. Content marketing attract consumers in a creative and informative way influencer marketing expands the market through recommendations from trusted figures, and viral marketing takes advantage of trends to disseminate information widely. Keywords: Content Marketing, Influencer Marketing, Viral Marketing, Purchasing Decisions.